2022
DOI: 10.3389/fsurg.2021.811706
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Endoscopic Endonasal Decompression of the Optic Canal, Superior Orbital Fissure, and Proper Orbital Apex for Traumatic Orbital Apex Syndrome: Surgical Anatomy and Technical Note

Abstract: ObjectivesTraumatic orbital apex syndrome (TOAS) is an uncommon but severe ocular complication of craniomaxillofacial fracture. The optimal surgical strategy for TOAS has not been determined. To investigate the endoscopic anatomy of the orbital apex region, propose a protocol for simultaneous endoscopic endonasal decompression of the optic canal, superior orbital fissure, and proper orbital apex (EEDCFA) for TOAS and report its use in two patients.MethodsAn endoscopic endonasal approach was utilized to dissect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
(29 reference statements)
0
3
0
Order By: Relevance
“…Muller's muscle is considered a marker for identifying the optic strut, the maxillary strut and the superior orbital fissure, but it is rarely used clinically (24,25). Liu et al described a "π" structure for the identification of the optic canal, the superior orbital fissure and the orbital apex (10). Alfieri et al explained in detail the composition of the "optic strut triangle" under the transnasal endoscope, which is essential in clinical work and this study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Muller's muscle is considered a marker for identifying the optic strut, the maxillary strut and the superior orbital fissure, but it is rarely used clinically (24,25). Liu et al described a "π" structure for the identification of the optic canal, the superior orbital fissure and the orbital apex (10). Alfieri et al explained in detail the composition of the "optic strut triangle" under the transnasal endoscope, which is essential in clinical work and this study.…”
Section: Discussionmentioning
confidence: 99%
“…It is, therefore, plausible to suggest that optic strut drilling is necessary to achieve a satisfactory decompression of the oculomotor nerve fissure segment. At present, decompression surgeries of the superior orbital fissure, orbital apex and optic canal are also performed in some cases of traumatic oculomotor nerve palsy, achieving good results (10,29), but none of them involve optic strut drilling. It was found that 270°decompression could be achieved after the optic strut was ground (Figure 1A), and the medial margin of the oculomotor nerve fissure segment could be sufficiently decompressed after the orbital apex and superior orbital fissure were ground in turn.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation